La pedagogía crítica en instituciones escolares de la parroquia de Calderón. - Zambrano, Jenny E. (2022)
Most of the educational institutions in the parish of Calderón have adopted the constructivist model as a pedagogical current in which teachers provide the necessary tools to their students so that they can learn from their own experiences, but we are forgetting to form critical, analytical, creative and reflective students, Critical Pedagogy favors the development of a critical conscience so that they are able to take ownership of learning, but it is also important that the teacher in his praxis considers social interaction, since, taking into account that language is an important factor for the development of human capabilities and also provides the opportunity to be skilled communicators, in the educational context focusing its attention on the horizontal dialectical discourse. Therefore, the objective of this research is to determine that the application of critical pedagogy in educational praxis favors the development of critical thinking, even more so, when it comes to giving importance to the opinion of students through dialogue within the teaching and learning process. A survey was conducted to collect data from 26 teachers from fiscal, fiscal-commissioned and private institutions in the parish of Calderon using the quantitative approach through the Google forms platform to determine if they use Critical Pedagogy in their educational praxis, with which we were able to determine that teachers use this pedagogy, however, they still consider the use of memory as a mechanism to prepare for an evaluation although some consider that teachers should develop critical thinking to develop cognitive skills. Thus, teachers must be prepared and updated because education also advances.